2011
DOI: 10.1097/scs.0b013e31821cc2b5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Outcomes of Blowout Fracture Repair According to the Orbital Implant

Abstract: Both Macropore and Medpor were associated with equally safe and satisfactory patient outcomes without notable complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…35 Advantages include ease in modeling and adapting. 42 Previous studies have shown long-term stability and tensile strength. No significant change in orbital volume has been found in long-term follow-up.…”
Section: Porous Polyethylenementioning
confidence: 99%
“…35 Advantages include ease in modeling and adapting. 42 Previous studies have shown long-term stability and tensile strength. No significant change in orbital volume has been found in long-term follow-up.…”
Section: Porous Polyethylenementioning
confidence: 99%
“…There is a general consensus that the ideal material for the repair of the blow-out fractures should: be strong enough to support the orbital contents; have sustainable mechanical properties; have a short setting time; be noncarcinogenic and biocompatible (Han and Chi, 2011;Tanag et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Porous polyethylene is easy to mold and adapt and allows rigid fixation and vascular ingrowth; however, it may form adhesions to exposed extra ocular muscles. [75][76][77][78] Titanium mesh implants, in contrast, are biocompatible and easy to contour, but are not easy to place, especially with deep orbital fractures, as the plate edges often catch on periorbital tissues. Also, titanium can be associated with intense fibrosis, making secondary surgery a challenge.…”
Section: Permanentmentioning
confidence: 93%
“…Implantassociated infections include implant migration, infection, exposure, palpability, or local inflammatory reaction, as outlined above. [72][73][74][75][76][77][78][79][80][81][82][83][84][85] Serious complications include postoperative optic neuropathy, blindness, and retrobulbar hema toma. Although rare, these should be discussed in detail with each patient and treatment plans should be individualized to minimize risks and maximize outcomes.…”
Section: Complicationsmentioning
confidence: 99%